Ritual Practices Within the Frame of Pilgrimage to the Tombs of the Just in Judaism (المجلة الدولية للبحوث العلمية, 2024)
The article explores the associated beliefs and rituals, Shrines are the graves of righteous saints among the Jews. The practices and rituals performed by visitors to the graves of the righteous among the Jews were analyzed and discussed, and these actions were discussed extensively so that the reader would forget to understand the nature of these rituals and actions that take place at the grave of the righteous according to the point of view, religion, justice and traditions of the Jewish religion. It must be noted that to this day, there are still many people who still perform and in similar practices participate. Relationships existing between different population groups.